Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1155/2014/562062
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intraoperative Anterior Segment Optical Coherence Tomography during Descemet's Stripping Automated Endothelial Keratoplasty

Abstract: Purpose. To examine the graft-host interface during Descemet's stripping automated endothelial keratoplasty (DSAEK) surgery with optical coherence tomography (OCT). Design. Prospective, interventional case series. Patients and Methods. Eight patients who underwent a DSAEK were included. A handheld OCT was used intraoperatively to examine the presence of interface fluid between the host cornea and the graft. Results. In 3 patients, no interface fluid was detected between the host cornea and the graft after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
(13 reference statements)
0
11
0
Order By: Relevance
“…6 Other case series have successfully used iOCT to show interface fluid drainage after corneal stab incisions. 11, 12 Similarly, Ide et. al.…”
Section: Discussionmentioning
confidence: 90%
“…6 Other case series have successfully used iOCT to show interface fluid drainage after corneal stab incisions. 11, 12 Similarly, Ide et. al.…”
Section: Discussionmentioning
confidence: 90%
“…The wound interface pattern can be shown by AS-OCT during DSAEK [ 36 ] or after PKP. Miyakoshi et al [ 39 ] suggested that AS-OCT is useful for detecting the interface fluid between the host cornea and the graft during a DSAEK. Similarly, Sung and Yoon [ 40 ] showed that the alignment pattern of the wound interface after PKP differed according to the clinical diagnosis before surgery.…”
Section: Assessment Of Descemet's Membrane: Descemet's Membrane Dementioning
confidence: 99%
“…AS‐OCT may be used to predict Descemet's stripping automated endothelial keratoplasty graft failure by elucidating the presence of residual host membrane tissue at the graft . Miyakoshi et al have also proposed AS‐OCT as a means of detecting fluid between the host‐donor interface in Descemet's stripping automated endothelial keratoplasty . Knecht et al have reported on the use of hand‐held AS‐OCT for this purpose .…”
Section: Resultsmentioning
confidence: 99%